1987
DOI: 10.1104/pp.83.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Abscisic Acid and Indoleacetic Acid in Cotton Fruits and Their Abscission Zones in Relation to Fruit Retention

Abstract: An experiment was conducted with field-grown cotton (Gossypium hirsutum L.) to determine the effects of drought and an increase in available photosynthate on the abscisic acid (ABA) and indoleacetic acid (IAA) contents of 3-day-old bolls and their abscission zones. Photosynthate availability was manipulated by removing about two-thirds of the plants to permit increased irradiance, and thus photosynthesis, in the plant canopy. The demand for photosynthate was decreased by removing all bolls from the remaining p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…However, from 8 to 15 DAA, concentrations of ABA increased in aborting and decreased in nonaborting kernels. Therefore, ABA may promote kernel abortion after it has been initiated just as it promotes boll abscission in cotton (10). The increase of ABA in aborting kernels was coincident with accumulation of reducing sugars in the cob of aborting kernels.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, from 8 to 15 DAA, concentrations of ABA increased in aborting and decreased in nonaborting kernels. Therefore, ABA may promote kernel abortion after it has been initiated just as it promotes boll abscission in cotton (10). The increase of ABA in aborting kernels was coincident with accumulation of reducing sugars in the cob of aborting kernels.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, IAA may promote continued growth of nonaborted kernels, but levels may be insufficient in aborted kernels to counteract growth inhibition. Similarly, it has been reported that IAA in the abscission zones of cotton bolls is positively correlated with boll retention (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The week immediately following anthesis appears to be a critical time in the development of each young boll because its IAA content is naturally low during this stage of development. Stresses, such as water deficit or an inadequate supply of photosynthate, were shown to decrease the free IAA content of young bolls and their abscission zones to even lower values and increase the percentage that abscised (17). Large flower buds and older bolls are much less likely than young bolls to abscise during periods of stress (12,16,22), probably at least in part because they contain much higher concentrations of IAA.…”
Section: Resultsmentioning
confidence: 99%
“…Water deficiency also changes the status of internal hormonal balance in the plant (Mcmichael et al, 1972;Guinn, 1976;Guinn and Brummett, 1988;Guinn et al, 1990). It enhances the rate of ethylene production (Guinn, 1976), increases abscisic acid (ABA) content in young cotton bolls and decreases the free indole-3-acetic acid (IAA) content (Guinn, 1982;Brummett, 1987 and1988). In sesame, abscission could be manipulated by altering the level of IAA and ethylene (Sexton and Roberts, 1982) .…”
mentioning
confidence: 99%